Food Insecurity and Participation in Community Food Programs among Low-income Toronto Families - Kirkpatrick, Sharon I. (Can J Public Health, 2009)
OBJECTIVES: Responses to food insecurity in Canada have been dominated by community-based food initiatives, while little attention has been paid to potential policy directions to alleviate this problem. The purpose of this paper is to examine food security circumstances, participation in community food programs, and strategies employed in response to food shortages among a sample of low-income families residing in high-poverty Toronto neighbourhoods. METHODS: Data from surveys conducted with 484 families and neighbourhood mapping were analyzed. RESULTS: Two thirds of families were food insecure over the past 12 months and over one quarter were severely food insecure, indicative of food deprivation. Only one in five families used food banks in the past 12 months and the odds of use were higher among food-insecure families. One third of families participated in children’s food programs but participation was not associated with household food security. One in 20 families used a community kitchen, and participation in community gardens was even lower. It was relatively common for families to delay payments of bills or rent and terminate services as a way to free up money for food and these behaviours were positively associated with food insecurity. DISCUSSION: While documenting high rates of food insecurity, this research challenges the presumption that current community-based food initiatives are reaching those in need. Public health practitioners have a responsibility to critically examine the programs that they deliver to assess their relevance to food-insecure households and to advocate for policy reforms to ensure that low-income households have adequate resources for food.